(untitled) (Research, Society and Development, 2022)
Microvarises are small dilated vessels, located under the skin of the lower limbs, with purple color and dimensions between 2 and 5 mm. Telangiectasias, on the other hand, are dilations of capillaries, arteries or veins smaller than 2mm in caliber, have a linear and sinuous arrangement and may form arachneiform, tangled or straight aspects. The appearance of varicose veins happens commonly in the population and is related to genetic predisposition. The microvessel injectable aesthetic procedure (PEIM) has been widely used to eliminate these smaller caliber vessels, mainly for aesthetic purposes. There are several sclerosing substances that are used for this treatment, including hypertonic glucose 50% and 75%, which is identified as one of the most important sclerosing agents, as it is an efficient and safe product. Treatment with 50% glucose can be a little slower because of its low concentration, whereas 75% glucose is more often used because it has satisfactory results from the first application. Therefore, the main objective of this article is to demonstrate how the PEIM procedure, together with the use of glucose, can be a key factor in solving microvessel problems.